A SYSTEMS APPROACH TO INCLUSIVE EDUCATION IN INDONESIAN PRIMARY SCHOOLS: A CASE STUDY - Novianti, Nita; Supena, Asep; Edwita, Edwita; Bintoro, Totok; Yatimah, Durotul (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
Inclusive education plays a crucial role in promoting equity in education, meaning that every childregardless of the ir physical, mental, or social condition has equal access to educational opportunities. This study aims to analyze the implementation of inclusive education using a systems approach at SD Islam Fathia, Sukabumi City. A descriptive qualitative method was employed, with data collected through interviews, observations, questionnaires, and documentation. The findings indicate that the systems approach, as outlined by Kaufman (1972), was applied in six key stages: (1) needs identification; (2) problem selection; (3) identification of problem-solving requirements; (4) formulation of alternative solutions; (5) periodic evaluation of inclusive education; and (6) revision of school policies. The systems approach proved effective in comprehensively identifying needs and solutions across the dimensions of input, process, and output. These were operationalized through inclusive culture, policies, and evidence-based practices. The study recommends strengthening collaboration among multidisciplinary stakeholders (schools, teachers, parents, specialists, and government) to support sustainable inclusive education. Additional recommendations include improving school facilities and infrastructure, increasing government support through teacher training, enhancing cross-sectoral collaboration, and developing written school-level policies. This research contributes to the development of a systems-based model for inclusive education at the primary school level.